Persepsi Dan Minat Pelaku UMKM Pengolahan Hasil Ternak Terhadap Sertifikasi Halal Di Kota Kediri - Chanifan Ibadi Fajar Herlambang; Siti Azizah (Lembaga Pengembangan Kinerja Dosen, 2024)
Kediri City is considered to have significant potential for developing a halal market industry. The Muslim population in Kediri City is reported to be 271,215 according to the 2022 data on Subdistricts and Religions Practiced in Kediri City. With the majority of the population in Kediri City being Muslim, this presents a great opportunity for micro, small, and medium-sized enterprises (MSMEs) to continue developing their products to meet the community's needs for halal products in Kediri City. This research aims to understand the perceptions and interests of MSMEs players in livestock product processing regarding halal certification in Kediri City, using a qualitative method. Sample selection for this research utilized purposive sampling and snowball sampling. There were two types of informants in this study: 2 (two) expert informants, consisting of the Cooperative and MSMEs Office and the local Ministry of Religion, and 10 (ten) key informants, namely MSMEs actors in livestock product processing business. According to Article 4 of the UUJPH (Halal Product Assurance Law), products entering, circulating, and traded in Indonesia's territory must have halal certification. The halal label can have a positive impact on businesses as it is considered to enhance consumer trust in products with the halal label. Based on the research results, MSMEs players in livestock product processing business in Kediri City feel a lack of knowledge due to the government's insufficient comprehensive dissemination to every element of society.